Analisis Kesulitan Strategi Pembelajaran Inquiry Discovery Sebagai Upaya Meningkatkan Kemandirian Belajar Siswa SD - Yeni Nuraeni; Luqman Kurniandrawan Nurhakim; Aisyah fitri yani; Dwi maya ariyanti; Riska Amalia (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2025)
This study aims to examine the effectiveness of the Inquiry Discovery learning strategy in enhancing the learning independence of elementary school students. The Inquiry Discovery learning model emphasizes students' active role in the process of discovering and investigating learning concepts through the stages of asking questions, collecting data, analyzing, and drawing conclusions independently. With this approach, students are encouraged to develop critical thinking skills and take responsibility for their own learning process. The results show that the implementation of the Inquiry Discovery model significantly increases students' learning independence through improved abilities to formulate problems, generate hypotheses, and actively explore material. This improvement also has a positive impact on students' learning motivation and self-confidence in facing learning challenges. The teacher acts as a facilitator who guides without taking over the student's learning role, thus strengthening independence in learning from an early age. These findings recommend the use of the Inquiry Discovery strategy as a primary choice in the learning process in elementary schools to develop independent, critical, and creative students.